Actuators, IoT and IP Address as Training in Actuators, IoT and IP Address for Senior High School Teachers and StudentsBasic Industrial Instrumentation - Waluyo, Waluyo; Widura, Andre; Aryanta, Dwi; Darlis, Arsyad Ramadhan; Subarna, Nana; Rustamaji, Rustamaji; Sawitri, Kania; Fauziah, Dini; Syahrial, Syahrial; Syafitri, Niken; Hadiatna, Febrian (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2020)
The third mission of a university is a community service. Based on this mission, this paper presents the activity of community service. The activity was training for senior high school students and teachers. The subjects of the training are actuators, IoT, and IP address. These components or subsystems are very important basic industrial instrumentation for further automation. These subsystems are very correlated with each other. Some actuators are electric, hydraulic, and pneumatic types. There are many applications of IoT and IP addresses, such as smart grids and communications.